CURRENT STATUS OF KNOWLEDGE ON PRESSURE ULCER PREVENTION AND RELATED FACTORS AMONG PRIMARY CAREGIVERS OF STROKE PATIENTS AT NAM DINH GENERAL HOSPITAL IN 2025 (Vietnam Journal of Community Medicine, 2026)
Objectives: This study describes the current state of knowledge and identifies somefactors related to knowledge about preventing pressure ulcers among primary caregivers ofstroke patients at Nam Dinh General Hospital in 2025. Methods: This is a cross-sectionaldescriptive study using a convenient sampling method and a pre-designed toolkit. Results:94.1% of primary caregivers correctly defined pressure ulcers, 86.7% correctly identifiedfactors that promote ulcer development, and 67.4% knew the causes of ulcers. 89.6% of studyparticipants correctly understood the role of the caregiver, 89.6% correctly answered about theappropriate time to change the position of wheelchair users, and only 36.3% of caregiverscorrectly knew about ulcer prevention diets. Furthermore, 15.5% of caregivers had poorknowledge regarding mobility-related pressure ulcer prevention. The study found a positivecorrelation between education level and length of care with the primary caregiver's knowledge.Conclusion: Regarding knowledge of preventing pressure ulcers among stroke patients, 71.1%of caregivers met the requirements and 28.9% did not. Educational level and length of carewere related to the level of knowledge of caregivers.
Keywords: Pressure ulcers, prevention, knowledge.